Expansions of key protein families in the German cockroach highlight the molecular basis of its remarkable success as a global indoor pest. Issue 5 (11th July 2018) - Harrison, Mark C.; Arning, Nicolas; Kremer, Lukas P. M.; Ylla, Guillem; Belles, Xavier; Bornberg‐Bauer, Erich; Huylmans, Ann Kathrin; Jongepier, Evelien; Piulachs, Maria‐Dolors; Richards, Stephen; Schal, Coby
Abstract: The German cockroach, Blattella germanica, is a worldwide pest that infests buildings, including homes, restaurants, and hospitals, often living in unsanitary conditions. As a disease vector and producer of allergens, this species has major health and economic impacts on humans. Factors contributing to the success of the German cockroach include its resistance to a broad range of insecticides, immunity to many pathogens, and its ability, as an extreme generalist omnivore, to survive on most food sources. The recently published genome shows that B. germanica has an exceptionally high number of protein coding genes. In this study, we investigate the functions of the 93 significantly expanded gene families with the aim to better understand the success of B. germanica as a major pest despite such inhospitable conditions. We find major expansions in gene families with functions related to the detoxification of insecticides and allelochemicals, defense against pathogens, digestion, sensory perception, and gene regulation. These expansions might have allowed B. germanica to develop multiple resistance mechanisms to insecticides and pathogens, and enabled a broad, flexible diet, thus explaining its success in unsanitary conditions and under recurrent chemical control. The findings and resources presented here provide insights for better understanding molecular mechanisms that will facilitate more effective cockroach control. GRAPHICAL ABSTRACT: Many gene families linked to insecticide resistance, immunity, sensory perception, and digestion are expanded in the German cockroach. These findings pinpoint some of the molecular mechanisms supporting the extraordinary success of this global pest.